Hydro-economic models for decision making on water optimization in Indus Basin: Examples from “Releasing water from high delta crops for other beneficial uses: Potential and Challenges seen in a computable general equilibrium (CGE) model” with extended analyses - Davies, Stephen; Akram, Iqra; Ali, Muhammad Tahir; Hafeez, Mohsin; Ringler, Claudia (International Food Policy Research Institute, 2024)
A (virtual) presentation for the CGIAR Nexus Gains Initiative Work Package . IWMI Headquarters, Lahore, Pakistan on April 18, 2024.